The fast track to new skills : short-cycle higher education programs in Latin America and the Caribbean - Ferreyra, Maria Marta (World Bank Publications, 2021)
Higher education in Latin America and the Caribbean (LAC) has expanded dramatically in the new millennium, yet enrollment in short-cycle programs (SCPs) is still relatively low. Shorter and more practical than bachelor's programs, SCPs can form skilled human capital fast. The economic crisis created by the COVID-19 pandemic has accentuated underlying trends, such as automation, the use of electronic platforms, and the need for lifelong learning. Addressing these demands requires the urgent upskilling and reskilling of the population-a task for which SCPs are uniquely suited. This publication explores the labor market out-comes and returns of SCPs, examines their providers, and identifies the practices adopted by the best programs. Relying on unique data that includes a novel survey of SCP directors in five LAC countries, it finds that while SCPs generate, on average, good labor market out-comes, they vary greatly in quality. SCP providers respond quickly and flexibly to local economy needs; and specific practices related to faculty, job search assistance, and interaction with prospective employers are distinctive of the best programs. Drawing on these findings, The Fast Track to New Skills discusses how to create an environment where good programs are offered and students have the interest and means to attend them. It draws attention to a higher education sector that has been typically overlooked, both in research and policy. The Fast Track to New Skills will be of interest to policy makers, researchers, and the public at large.